The Use of a Pair of 3D-Printed Near Field Superstructures to Steer an Antenna Beam in Elevation and Azimuth - Touseef Hayat (IEEE, 2021)
The paper presents a method to design beam-steering antennas using a pair of 3D printed perforated dielectric structures (PDSs) placed in the near-field region of a base antenna, which has a fixed beam. Detailed designs and quantitative comparison of two beam-steering antenna systems are presented. One antenna system has a conical horn antenna and the other uses a resonant-cavity antenna (RCA) as the base antenna. In both cases, the first PDS transforms the phase distribution of the aperture near field and hence tilts the antenna beam to an offset angle. The second PDS, placed above the first, introduces an additional linear progression to the phase of the near field. The two PDSs are rotated independently to steer the beam in both azimuth and elevation. The PDSs have been 3D-printed using acrylonitrile butadiene styrene (ABS) filaments. Each prototype was fabricated in about 16 hours, weighs 300 grams, and costs approximately 5.5 US Dollars. The measured results show that, at the operating frequency of 11 GHz, the RCA-based system has a peak gain of 17.7 dBi compared to the 16.6 dBi gain obtained with the horn-based system. In a fixed E-plane, the variation in the aperture near-field phase of the horn antenna (115°) is much less than that of the RCA (360°). This reduces the efforts required for phase correction and hence led to the former having a larger 3dB measured gain bandwidth of 1.2 GHz compared with the 0.7 GHz bandwidth of the latter, but at the cost of 35.6% increase in the total height of the antenna system.